Climate Risk Management in Agricultural and Livestock Extension (CRMALE) - Kenya Reference Guide - Hansen, James; Dinku, Tufa; Trzaska, Sylwia; Grossi, Amanda; Jensen, Nathaniel D.; Dione, Michel M.; Bett, Bernard K.; Dhulipala, Ram K.; Mohamed, Tahira Shariff; Derbyshire, Samuel F.; Huyer, Sophia; Moore, Maya; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Improvements in the weather and climate information available in Kenya provide new opportunities for agricultural extension personnel to help agricultural producers better manage the risks that they face, and to adapt recommended technology packages to local climatic conditions. This Reference Guide provides training materials for the 2-week course, Climate Risk Management in Agricultural and Livestock Extension (CRMALE). The course aims to equip agricultural extension workers to access, understand and incorporate climate information into their professional work. It is designed to provide foundational knowledge on climate and agricultural decision making; and practical tools to analyze climate-related risks, use appropriate weather and climate information to support agricultural decisions, communicate complex climate information effectively with crop and livestock farmers, and integrate climate services into agricultural extension activities. This course is designed for agricultural extension professionals who actively support crop and livestock producers with information, advice and other services. It targets extension agents working at the ward and sub-county levels within Kenya’s public sector agricultural extension service, and non-government extension and advisory service professionals with a comparable background.